Lactobacillus plantarum ZJUIDS14 alleviates non-alcoholic fatty liver disease in mice in association with modulation in the gut microbiota - Cao, Feiwei; Ding, Qinchao; Zhuge, Hui; Lai, Shanglei; Chang, Kaixin; Le, Chunyan; Yang, Guorong; Valencak, Teresa G.; Li, Songtao; Ren, Daxi (Frontiers in Nutrition, 2023)
This present study was designed to explore the protective role of Lactobacillus plantarum ZJUIDS14 against Non-alcoholic Fatty Liver Disease (NAFLD) in a high-fat-diet (HFD)-induced C57BL/6 mice model. The probiotic (109 CFU/every other day) was administered by oral gavage for 12 weeks. We found that L. plantarum ZJUIDS14 intervention significantly alleviated HFD related hepatic steatosis, liver damage, insulin resistance, and increased hepatic expression of peroxisome proliferator activated receptor α (PPAR-α) while stimulating the activation of AMP-activated protein kinase (AMPK). Furthermore, L. plantarum ZJUIDS14 improved mitochondrial function as reflected by an increase in dynamin related protein 1 (DRP1) and a decrease of proteins associated with oxidative phosphorylation (OXPHOS) after the treatment. Additionally, mice from the L. plantarum ZJUIDS14 group had a restored intestinal flora and homeostasis involving Coprostanoligenes group, Ruminococcaceae UCG-014, Allobaculum, Ruminiclostridium 1, and Roseburia. Meanwhile, these five genera exhibited a significant (negative or positive) association with ileum inflammation mRNA levels and SCFA contents, by Spearman’s correlation analysis. In general, our data demonstrate that L. plantarum ZJUIDS14 mitigates hepatic steatosis and liver damage induced by HFD. Specifically, they strengthened the integrity of the intestinal barrier, regulated gut microbiota, and improved mitochondrial function. Our data provide an experimental basis for L. plantarum ZJUIDS14 as a promising candidate to prevent NAFLD.